2021
DOI: 10.14218/jcth.2021.00171
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nonalcoholic Fatty Liver Disease on the Occurrence and Severity of Chronic Kidney Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is reported to affect 20-30% of adults and is accompanied by various metabolic comorbidities, where the economic and clinical burden of NAFLD is attributed to the progression of liver disease as well as the presence of extrahepatic diseases. Chronic kidney disease (CKD), which has a high incidence rate, high morbidity and mortality rates, and high medical costs, has been linked to NAFLD. CKD is associated with some metabolism-related risk factors that overlap with metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 109 publications
0
13
0
Order By: Relevance
“…Over the last decades, several epidemiological studies and some meta-analyses have clearly reported that NAFLD (detected by blood biomarkers/scores, imaging techniques, International Classification of Diseases codes or liver biopsy) is associated with an increased risk of incident CKD, independent of established CKD risk factors, diabetes-related variables and other potential confounders [21][22][23][24][25]. Notably, as previously mentioned, the association between NAFLD and CKD have relevant clinical implications, as both NAFLD and CKD are two important global health problems with the worryingly direction to become more and more frequent worldwide [21].…”
Section: Association Between Nafld and Risk Of Incident Ckdmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the last decades, several epidemiological studies and some meta-analyses have clearly reported that NAFLD (detected by blood biomarkers/scores, imaging techniques, International Classification of Diseases codes or liver biopsy) is associated with an increased risk of incident CKD, independent of established CKD risk factors, diabetes-related variables and other potential confounders [21][22][23][24][25]. Notably, as previously mentioned, the association between NAFLD and CKD have relevant clinical implications, as both NAFLD and CKD are two important global health problems with the worryingly direction to become more and more frequent worldwide [21].…”
Section: Association Between Nafld and Risk Of Incident Ckdmentioning
confidence: 99%
“…In literature, several narrative reviews have already described the biological mechanisms underpinning the association between NAFLD/MAFLD and the risk of CKD [21,[23][24][25]. Here, we will limit ourselves to describing the salient aspects of this topic (Figure 1).…”
Section: Putative Mechanisms Underpinning the Association Between Naf...mentioning
confidence: 99%
See 3 more Smart Citations